Reducing grains/loss asymmetry: A virtual reality choice experiment (VRCE) valuing land use change - Ian J. Bateman; Andy P. Jones; Simon Jude; Brett H. Day (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2006)
Recent research suggests that, in some situations, numeric information may lack the 'evaluability' of visual representations of the same data. In such cases, reliance upon numeric information exacerbates tendencies for survey respondents to rely upon heuristics rather than their underlying preferences in formulating responses. Adapting such insights to the field of non-market valuation, for certain environmental goods, information on increases or decreases in the numeric levels of an attributes may trigger reliance upon the loss aversion heuristic, leading to an exacerbation of the well know gains/loss asymmetry problem (Horowitz and McConnell, 2002). A split sample choice experiment (CE) is described in which standard approaches to conveying a land use change scenario (relying principally on numeric information) are contrasted with an alternative treatment in which objectively identical information is presented in visual form via virtual reality (VR) visualisations. A third treatment combines both formats. Results show that the gains/loss asymmetry is roughly twice as strong under a conventional numeric CE design than in the presence of visual information. The combined VRCE methodology developed in the paper therefore significantly ameliorates this pervasive anomaly and, we contend, represents an exciting prospect for the incorporation of complex real world environments within economic analyses.
Keywords: 330; Choice Experiments; coastal zones; Gains/loss asymmetry; land use change; loss aversion; Non-market valuation; virtual reality